Pengaruh Konsentrasi dan Waktu Penyemprotan Pupuk Organik Cair Super ACI terhadap Pertumbuhan dan Hasil Jagung Manis - RAHMI, ABDUL; -, JUMIATI (AGRITROP, 2012)
The objectives of experiment were: (1) to understand of effect concentration and timing of application of Super ACI foliar organic fertilizer, and (2) to determined of concentration and timing application of Super ACI foliar organic fertilizer to sweet corn. The experiment was conducted at Rawa Makmur Village, Palaran Sub District, Samarinda City, on July 2004 until October 2004. The experiment design used was Completely Randomized Block Design in Faktorial Experiment 4 x 3 with three replications. The first factor was concentration of Super ACI (K) consisted 4 levels, namely: no Super ACI application (k0), 0,71 ml l-1 water (k1), 1,43 ml l-1 water (k2), and 2,15 ml l-1 water (k3). The second factor was timing of application (W) consisted 3 levels, namely : 12, 24, and 36 days after planting (w1), 15, 30, and 45 days after planting (w2), and 18, 36 and 54 days after planting. The result of experiment showed that: (1) the concentration of Super ACI was significantly on the plant height at 42 days after planting, blooming time of male and female, harvest time, length of cob, diameter of cob, weight of cob, and affected significantly on the yield of cob. The highest of cob yield namely 8,77 ton ha-1 was achieved on 1,43 ml l-1 water of Super ACI; (2) timing of application was no significant on the plant height at 14, 28, and 42 days after planting, blooming time of male and female, harvest time, length of cob, diameter of cob, weight of cob, and yield of cob; and (3) no interaction between concentration and timing of application of Super ACI foliar organic fertilizer on the all parameters.
Keywords: Super ACI Foliar Organic Fertilizer, Sweet Corn